1987
DOI: 10.1128/jb.169.8.3770-3777.1987
|View full text |Cite
|
Sign up to set email alerts
|

Identification and partial characterization of a novel bipartite protein antigen associated with the outer membrane of Escherichia coli

Abstract: A study by crossed immunoelectrophoresis performed in conjunction with precipitate excision and polypeptide analysis identified a new antigen complex in the envelope of Escherichia coli ML308-225. This antigen corresponds to antigen 43 in the crossed immunoelectrophoresis profile of membrane vesicles (P. Owen and H. R. Kaback, Proc. Natl. Acad. Sci. USA 75:3148-3152, 1978). Immunoprecipitation experiments conducted with specific antiserum revealed that the complex was expressed on the cell surface and that it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 30 publications
2
43
0
Order By: Relevance
“…As such, antigen 43 was one of the first autotransporters identified, however, it was not until much later that its mode of biogenesis was uncovered (204). In the intervening period, much time was invested in the biochemical characterization of this protein; Owen and coworkers (54,370) demonstrated that antigen 43 existed as a bipartite complex of two proteins (termed ␣ 43 and ␤ 43 ) which could be resolved under denaturing conditions. These subunit proteins were found to exist in a stoichiometric fashion at a ratio of 1:1, and the interaction between the two proteins was noncovalent.…”
Section: Antigen 43mentioning
confidence: 99%
“…As such, antigen 43 was one of the first autotransporters identified, however, it was not until much later that its mode of biogenesis was uncovered (204). In the intervening period, much time was invested in the biochemical characterization of this protein; Owen and coworkers (54,370) demonstrated that antigen 43 existed as a bipartite complex of two proteins (termed ␣ 43 and ␤ 43 ) which could be resolved under denaturing conditions. These subunit proteins were found to exist in a stoichiometric fashion at a ratio of 1:1, and the interaction between the two proteins was noncovalent.…”
Section: Antigen 43mentioning
confidence: 99%
“…The complex differs from the well-characterized proteins of the outer membrane of E. coli in that it consists of two different subunits (31,41). In addition, the antigen is surface exposed, and its yield varies in a manner which appears to be independent of external growth conditions.…”
mentioning
confidence: 98%
“…The polypeptide is heat modifiable and shows an apparent Mr of 37,000 when solubilized at temperatures lower than 70°C before analysis by sodium dodecyl sulfate (SDS)-polyacrylamide gel electrophoresis. Analysis by CIE performed in conjunction with zymogram staining and radiolabeling failed to detect the presence of enzyme activity, fatty acyl groups, or other cofactors for the complex (41).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ag43 is composed of two subunits, α and β, which are encoded by a single gene, agn43 (formerly called flu) in E. coli K-12, M. Gabig and others and maturation requires removal of the N-terminal signal peptide and proteolytic cleavage of the remaining polypeptide (Caffrey & Owen, 1989 ;Henderson et al, 1997). The 43 kDa α subunit is surface-expressed and is attached to the cell through an interaction between its C-terminal domain and the 43 kDa β subunit, an integral outer-membrane protein (Caffrey & Owen, 1989 ;Owen et al, 1987). Presentation of Ag43 on the cell surface is responsible for the so-called ' frizzy ' or form 1 phenotype (Diderichsen, 1980 ;Henderson et al, 1997 ;Warne et al, 1990).…”
Section: Introductionmentioning
confidence: 99%